The Development Prototype of Smart Lighting Control System (SLCS) with IoT-based Application - Md Saaid, Nurnasuha; Abdullah, Mohd Noor (Evolution in Electrical and Electronic Engineering, 2023)
The goal of this research project is to create a prototype for a smart lighting control system that incorporates Internet of Things (IoT) technologies. The prototype incorporates LED luminaires outfitted with light sensors and passive infrared (PIR) sensors, allowing automatic switching of the AC bulb based on observed light levels and movement. Furthermore, the system employs Blynk Apps as an IoT application, allowing manual control of the AC light via smartphones. The prototype was tested and evaluated in a controlled laboratory environment, using multiple scenarios and metrics to validate its functionality and performance. The results proved the prototype's ability to detect light levels below the 185-lux threshold and movement using the PIR sensor. Furthermore, the integration of the Blynk Apps IoT application demonstrated the AC bulb's flawless control via smartphone contact. The feedback from the testing phase generated tweaks and enhancements to assure the prototype's dependability and usability. Overall, by demonstrating the successful integration of sensors and IoT technology, this research study contributes to the growth of smart lighting technology and IoT applications, paving the way for more efficient and convenient smart lighting solutions in a variety of contexts.